Pengaruh Struktur Kepemilikan Dalam Mekanisme Corporate Governance Terhadap Cost Of Equity Capital - tarjo tarjo (AKRUAL: JURNAL AKUNTANSI, 2009)
AbstractCorporate governance mechanisms believed to have strong impact to the companies performance. Corporate governance mechanisms examined in this study are managerial ownership and institutional ownership structure. The purposes of this study are to know the variables effect of managerial ownership and institutional ownership on cost of equity capital. The samples of the study are firms listed in Jakarta Stock Exchange in 2005. The F-test on the all variables at the level confidence 1% indicates the effect of all variables on cost of equity capital is significant. The result of this study showed that managerial ownership and institutional ownership have positive significant impact (at the level of confidence 1% and 5%) on the cost of equity capital. However this result showed that corporate governance mechanisms fail to decrease the cost of equity capital.